Toxicity of external beam accelerated partial-breast irradiation (APBI) in adjuvant therapy of early-stage breast cancer: prospective randomized study - Burkon, Petr; Selingerova, Iveta; Slavik, Marek; Holanek, Milos; Vrzal, Miroslav; Coufal, Oldrich; Polachova, Katerina; Muller, Petr; Slampa, Pavel; Kazda, Tomas (Radiation oncology (London, England), 2024)
BACKGROUND: Accelerated partial breast irradiation (APBI) is an alternative breast-conserving therapy approach where radiation is delivered in less time compared to whole breast irradiation (WBI), resulting in improved patient convenience, less toxicity, and cost savings. This prospective randomized study compares the external beam APBI with commonly used moderate hypofractionated WBI in terms of feasibility, safety, tolerance, and cosmetic effects. METHODS: Early breast cancer patients after partial mastectomy were equally randomized into two arms- external APBI and moderate hypofractionated WBI. External beam technique using available technical innovations commonly used in targeted hypofractionated radiotherapy to minimize irradiated volumes was used (cone beam computed tomography navigation to clips in the tumor bed, deep inspiration breath hold technique, volumetric modulated arc therapy dose application, using flattening filter free beams and the six degrees of freedom robotic treatment couch). Cosmetics results and toxicity were evaluated using questionnaires, CTCAE criteria, and photo documentation. RESULTS: The analysis of 84 patients with a median age of 64 years showed significantly fewer acute adverse events in the APBI arm regarding skin reactions, local and general symptoms during a median follow-up of 37 months (range 21-45 months). A significant difference in favor of the APBI arm in grade ≥ 2 late skin toxicity was observed (p = 0.026). Late toxicity in the breast area (deformation, edema, fibrosis, and pain), affecting the quality of life and cosmetic effect, occurred in 61% and 17% of patients in WBI and APBI arms, respectively. The cosmetic effect was more favorable in the APBI arm, especially 6 to 12 months after the radiotherapy. CONCLUSION: External APBI demonstrated better feasibility and less toxicity than the standard regimen in the adjuvant setting for treating early breast cancer patients. The presented study confirmed the level of evidence for establishing the external APBI in daily clinical practice. TRIAL REGISTRATION: NCT06007118.
Keywords: kombinovaná terapie; Infant; Humans; External beam radiotherapy; kojenec; Adjuvant radiotherapy; Quality of Life; Female; lidé; kvalita života; APBI; předškolní dítě; Breast Neoplasms; mastektomie; ženské pohlaví; segmentální mastektomie; nádory prsu; Combined Modality Therapy; Early breast cancer; prospektivní studie; Child, Preschool; Mastectomy, Segmental; Mastectomy; Surgical bed; Prospective Studies